One-component polyurethane adhesive
Patent Information
- Application Number
- CN202180070188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-14
- Filing Date
- 2021-08-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-08-18
AI Technical Summary
底漆在汽车OEM工厂中的使用增加了挥发性有机化合物、生产步骤、品质问题和制造成本
[0026]本发明的组合物可用于将玻璃和涂漆的基材粘结在一起而不需要底漆。组合物赋予满足工业标准的搭接剪切强度并且提供耐久的粘结。在优选实施例中,组合物在23℃±2℃下固化7天之后展现出6MPa(870psi)或更大的拉伸强度、3MPa(435psi)或更大的杨氏模量、2.5MPa(362psi)或更大的搭接剪切粘合强度和100%内聚失效、270%或更大的伸长率和在23℃和50%相对湿度和其他环境老化条件下固化7天之后100%内聚失效的快速刀粘合。本发明的组合物在室温下是可泵送的并且不需要加热。
Smart Images

Figure BDA0004175936250000071 
Figure BDA0004175936250000091 
Figure BDA0004175936250000092
Abstract
Description
Technical Field
[0001] This invention relates to the field of one-component polyurethane adhesives, and in particular to polyurethane adhesives for bonding to glass and acid-resistant coatings without the need for a primer. Background Technology
[0002] One-component polyurethane adhesives are widely used in the automotive industry, particularly for bonding windshields to window flanges on vehicle bodies. Commercial adhesives are designed to provide strong adhesion and good physical properties. To achieve good bond strength (overlap shear value >362 psi) and favorable failure modes, many adhesives require a primer on the glass frit of the windshield and the coated window flange. The use of primers in automotive OEM plants increases volatile organic compound emissions, production steps, quality issues, and manufacturing costs.
[0003] Adhesives that provide primerless bonding to glass frit or painted metal panels have been reported, but these adhesives lack primerless bonding performance for both glass frit and painted panels, especially for both bent glass frit and acid-resistant painted panels.
[0004] There is a strong need for a one-component polyurethane adhesive that can provide good primerless adhesion for both glass frit and painted panels. Summary of the Invention
[0005] In a first aspect, the present invention provides a one-component polyurethane adhesive composition comprising:
[0006] (A) At least one polyether prepolymer with a total content of 30-75 wt% of polyether prepolymer;
[0007] (B) At least one polyester prepolymer with a total content of 0.5-2.0 wt% of polyester prepolymer;
[0008] (C) At least one aliphatic polyisocyanate with a total aliphatic polyisocyanate content of 0.5-3.0 wt%.
[0009] (D) At least one aromatic polyisocyanate in total aromatic polyisocyanate content of 0.2-2.0 wt%.
[0010] (E) At least one isocyanate-functionalized silane with a total isocyanate-functionalized silane content of 0.2-3.0 wt%.
[0011] (F) 0.1-0.6 wt% amine catalyst
[0012] (G) at least one mercaptosilane with a total mercaptosilane content of 0-1.5 wt% and / or at least one aminosilane with a total aminosilane content of 0-1.5 wt%, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0013] (H) 10-35wt% carbon black;
[0014] (I) Optional 0-20 wt% calcium carbonate
[0015] (J) Optionally 0-20 wt% of fillers other than carbon black and calcium carbonate
[0016] (K) At least one organometallic catalyst, said catalyst being capable of catalyzing the reaction of isocyanates with functional groups having at least one active hydrogen and silane condensation;
[0017] The total polyisocyanate content is 1-5 wt%, the total amount of calcium carbonate and filler is 0-20 wt%, and the weight percentages are based on the total weight of the polyurethane adhesive.
[0018] In a second aspect, the present invention provides an adhesive assembly comprising:
[0019] Glass substrate;
[0020] Second substrate;
[0021] The adhesive composition of the present invention comprises a layer that is in adhesive contact with two substrates.
[0022] In a third aspect, the present invention provides a method for bonding a glass substrate to a second substrate, the method comprising the following steps:
[0023] (1) Provide a glass substrate and a second substrate;
[0024] (2) Applying the adhesive composition of the present invention to a primerless glass substrate, a second substrate, or both;
[0025] (3) Assemble the glass substrate and the second substrate such that the adhesive composition is bonded to the two substrates.
[0026] The compositions of this invention can be used to bond glass and painted substrates together without the need for a primer. The compositions impart lap shear strength meeting industry standards and provide durable adhesion. In preferred embodiments, the compositions exhibit a tensile strength of 6 MPa (870 psi) or greater, a Young's modulus of 3 MPa (435 psi) or greater, a lap shear bond strength of 2.5 MPa (362 psi) or greater, 100% cohesive failure, elongation of 270% or greater, and rapid knife bond with 100% cohesive failure after curing for 7 days at 23°C and 50% relative humidity and other environmental aging conditions. The compositions of this invention are pumpable at room temperature and do not require heating. Detailed Implementation
[0027] The inventors have unexpectedly discovered that the adhesive composition according to claim 1 imparts good primerless adhesion to both the glass and the painted substrate, even after environmental aging conditions.
[0028] Definitions and abbreviations
[0029] MDI 4,4′-methylenebis(phenyl isocyanate)
[0030] HDI hexamethylene diisocyanate
[0031] PU polyurethane
[0032] SEC size exclusion chromatography
[0033] The molecular weights of polymers reported herein are number-average or weight-average molecular weights in Daltons (Da), as determined by size exclusion chromatography (SEC).
[0034] The one-component polyurethane adhesive composition of the present invention comprises:
[0035] (A) At least one polyether prepolymer with a total content of 30-75 wt% of polyether prepolymer;
[0036] (B) At least one polyester prepolymer with a total content of 0.5-2.0 wt%.
[0037] (C) At least one aliphatic polyisocyanate with a total aliphatic polyisocyanate content of 0.5-3.0 wt%;
[0038] (D) At least one aromatic polyisocyanate with a total aromatic polyisocyanate content of 0.2-2.0 wt%;
[0039] (E) At least one isocyanate-functionalized silane with a total isocyanate-functionalized silane content of 0.2-3.0 w%;
[0040] (F) 0.1-0.6 wt% amine catalyst;
[0041] (G) at least one mercaptosilane with a total mercaptosilane content of 0-1.5 wt% and / or at least one aminosilane with a total aminosilane content of 0-1.5 wt%, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0042] (H) 10-35wt% carbon black;
[0043] (I) Optional 0-20 wt% calcium carbonate;
[0044] (J)Optional 0-20 wt% of fillers other than carbon black and calcium carbonate;
[0045] (K) At least one organometallic catalyst, said catalyst being capable of catalyzing the reaction of isocyanates with functional groups having at least one active hydrogen and silane condensation;
[0046] The total polyisocyanate content is 1-5 wt%, the total amount of calcium carbonate and filler is 0-20 wt%, and the weight percentages are based on the total weight of the polyurethane adhesive.
[0047] Polyether prepolymer (A)
[0048] Based on the total weight of the composition, the compositions of the present invention contain 30-75 wt% of polyether prepolymer.
[0049] Polyether prepolymers comprise polymers manufactured by polymerizing one or more polyether polyols in the presence of polyisocyanates, preferably diisocyanates. Polyether polyols usable in this invention include, for example, polyether polyols, poly(alkylene carbonate) polyols, hydroxyl-containing polysulfides, polymeric polyols, and mixtures thereof. Polyether polyols are well known in the art and include, for example, polyoxyethylene, polyoxypropylene, polyoxybutylene, and polytetramethylene ether glycols and triols, prepared by reacting unsubstituted or halogen- or aromatic-substituted ethylene oxide or propylene oxide with an initiator compound containing two or more active hydrogen groups, such as water, ammonia, a polyol, or an amine. Typically, polyether polyols can be prepared by polymerizing alkyl epoxides in the presence of an initiator compound containing active hydrogen. Preferred polyether polyols contain one or more alkyl epoxide units in the main chain of the polyol. Preferred alkyl epoxide units are ethylene oxide, propylene oxide, butylene oxide, and mixtures thereof. Preferably, the polyol contains propylene oxide units, ethylene oxide units, or mixtures thereof. In embodiments where the mixture of epoxide units is contained in the polyol, the different units may be randomly arranged or may be arranged in blocks of each epoxide. In a preferred embodiment, the polyol comprises propylene oxide chains, wherein the ethylene oxide chains are end-capped polyols. In a preferred embodiment, the polyether polyol is a mixture of polyether diol and polyether triol. Preferably, the polyether polyol or mixture has a functionality of at least about 1.5, more preferably at least about 1.8, and most preferably at least about 2.0; and preferably not greater than about 4.0, more preferably not greater than about 3.5, and most preferably not greater than about 3.0. Preferably, the equivalent weight of the polyether polyol mixture is at least about 200, more preferably at least about 500, and most preferably at least about 1,000; and preferably not greater than about 5,000, more preferably not greater than about 3,000, and most preferably not greater than about 2,500.
[0050] More specific examples include:
[0051] 1. Bifunctional polyols (diols), such as poly(epoxide) glycols in which the alkylene derivatives are C2 to C4, particularly poly(ethylene oxide) glycol, poly(propylene oxide) glycol, and poly(tetrahydrofuran) glycol, wherein poly(propylene oxide) glycol is particularly preferred. In a particularly preferred embodiment, the polyether prepolymer comprises a nominal bifunctional poly(propylene oxide) (equivalent weight 1000) having 56 hydroxyl groups;
[0052] 2. Trifunctional polyols (triols), such as those based on alkylene oxides initiated by trifunctional polyols (such as trimethylolpropane), wherein the alkylene derivative is C2 to C4, particularly ethylene oxide, propylene oxide, tetrahydrofuran, and butane oxide, wherein propylene oxide is particularly preferred. In a particularly preferred embodiment, the polyether prepolymer comprises a nominal trifunctional poly(propylene oxide) (equivalent weight 1558) having 36 hydroxyl groups; the polymer may or may not be end-capped with ethylene oxide to modify its reactivity.
[0053] 3.1 and 2. A mixture of 1 and 2 is particularly preferred, and even more particularly preferred is a mixture of a) a nominal difunctional poly(propylene oxide) having 56 hydroxyl groups (equivalent weight 1000) and b) a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups (equivalent weight 1558) (especially in a weight ratio of b) / a) of 1:2 to 2:1).
[0054] There are no particular limitations on the diisocyanates that can be used to manufacture polyether prepolymers. Aliphatic and aromatic diisocyanates can be used. Examples of suitable diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI) (hydrogenated MDI), and isophorone diisocyanate (IPDI), with MDI being particularly preferred.
[0055] In a particularly preferred embodiment, the polyether prepolymer comprises a nominal trifunctional poly(propylene oxide) having 56 hydroxyl groups (equivalent weight 1000) and a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups (equivalent weight 1558) reacted with MDI.
[0056] In a preferred embodiment, the polyether prepolymer has an isocyanate content of 1.25% by weight and a viscosity of 16,000 cps at 23°C, as measured by the procedure described in column 12, lines 38 to 49 of U.S. Patent No. 5,922,809.
[0057] The polyether prepolymer is present at 30-75 wt%, more preferably 45-65 wt%, and more particularly preferably 55-64% (based on the total weight of the adhesive composition).
[0058] In a particularly preferred embodiment, the adhesive composition of the present invention comprises 58-64 wt% of a polyether prepolymer based on the total weight of the adhesive composition, the polyether prepolymer comprising a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups (equivalent weight 1558) and a nominal trifunctional poly(propylene oxide) having 56 hydroxyl groups (equivalent weight 1000), and having an isocyanate content of 1.25 wt% and a viscosity of 16,000 cps at 23°C as measured according to the procedure described in column 12, lines 38 to 49 of U.S. Patent No. 5,922,809.
[0059] Preferably, the prepolymer has a Brinell viscosity of at least 6,000 centipoise or at least about 8,000 centipoise, and at most 30,000 centipoise or at most 20,000 centipoise. If the viscosity is too high, the final adhesive will be difficult to pump. If the viscosity is too low, the final adhesive will be too flowable and / or will sag.
[0060] The prepolymer has an isocyanate equivalent weight of at least 840, corresponding to a NCO content of 5% by weight. The isocyanate equivalent weight of the prepolymer can be at least 1050 (NCO content 4%), at least 1400 (NCO content 3%), or at least 1680 (NCO content 2.5%), and can be up to, for example, 10,000 (NCO content 0.42%), up to 8400 (NCO content 0.5%), up to 7000 (NCO content 0.6%), or up to 5000 (NCO content 0.84%). The polyether prepolymer has an average isocyanate functionality of at least about 2.0 and a molecular weight (weight average) of at least about 2,000. Preferably, the average isocyanate functionality of the prepolymer is at least about 2.2, and more preferably at least about 2.4. Preferably, the isocyanate functionality is not greater than about 3.5, more preferably not greater than about 3.0, and most preferably not greater than about 2.8. Preferably, the weight-average molecular weight of the prepolymer is at least about 2,500, and more preferably at least about 3,000; and preferably not greater than about 40,000, even more preferably not greater than about 20,000, more preferably not greater than about 15,000, and most preferably not greater than about 10,000. The prepolymer can be prepared by any suitable method, such as by reacting an isocyanate reactive compound containing at least two isocyanate reactive, active hydrogen groups with a polyisocyanate in excess of stoichiometry under reaction conditions sufficient to form the corresponding prepolymer.
[0061] The prepolymer equivalent weight and molecular weight were determined according to the procedure disclosed in column 12, lines 50 to 64 of U.S. Patent No. 5,922,809 (which is incorporated herein by reference).
[0062] Polyester prepolymer (B)
[0063] Based on the total weight of the composition, the adhesive composition of the present invention contains 0.5-2.0 wt% polyester prepolymer.
[0064] Polyester prepolymers include polymers produced by reacting one or more linear copolyesters having primary hydroxyl functional groups with polyisocyanates, preferably diisocyanates. Particularly preferred are copolyesters having a molecular weight of 3,000-4,000 Da, preferably 3,500 Da.
[0065] There are no particular limitations on the diisocyanates that can be used to manufacture polyester prepolymers. Aliphatic and aromatic diisocyanates can be used. Examples of suitable diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI) (hydrogenated MDI), and isophorone diisocyanate (IPDI), with MDI being particularly preferred.
[0066] In a preferred embodiment, the polyester prepolymer is produced by reacting a copolyester with a molecular weight of 3,500 Da with MDI. Preferably, it has a melting point of 45°C to 90°C.
[0067] The polyester prepolymer is present in 0.5-2.0 wt% of the total weight of the composition, preferably in 0.9-1.5 wt% of the total weight of the adhesive composition, and more preferably in 1-1.3 wt%.
[0068] In a preferred embodiment, the polyester prepolymer is produced by reacting a copolyester with a molecular weight of 3,500 Da with MDI, having a melting point of 45°C to 90°C, and is used at 1 to 1.3 wt% based on the total weight of the adhesive composition.
[0069] Aliphatic polyisocyanates (C)
[0070] The adhesive composition of the present invention contains at least one aliphatic polyisocyanate in a total aliphatic polyisocyanate content of 0.5-3.0 wt%.
[0071] There are no particular limitations on aliphatic polyisocyanates. Some examples include isophorone diisocyanate, 1,6-hexamethylene diisocyanate, bis(4-isocyanocyclohexyl)methane, and trimethylhexamethylene diisocyanate, any of which can be modified to include biuret, urethane, urea, carbamate, isocyanurate, or carbodiimide groups.
[0072] In a preferred embodiment, the aliphatic polyisocyanate is based on HDI trimer having an NCO content of 21.8 ± 0.3% (according to DIN EN ISO 11 909).
[0073] Aliphatic polyisocyanates are present in the adhesive compositions of the present invention at 0.5-3.0 wt% based on the total weight of the composition, preferably at 0.8-2.5 wt% based on the total weight of the adhesive composition.
[0074] In a particularly preferred embodiment, the aliphatic polyisocyanate is based on 0.8 to 2.5 wt% of HDI trimer of the total weight of the binder composition, having an NCO content of 21.8 ± 0.3% (according to DIN EN ISO 11 909).
[0075] Aromatic polyisocyanates (D)
[0076] The adhesive composition of the present invention comprises at least one aromatic polyisocyanate (D) based on a total aromatic polyisocyanate content of 0.2-2.0 wt% of the total aromatic polyisocyanate content of the adhesive composition.
[0077] There are no particular limitations on aromatic polyisocyanates. Examples include diphenylmethane diisocyanate (MDI), polymethylene polyphenyl isocyanate, polymeric MDI (PMDI, a mixture of diphenylmethane diisocyanate and polymethylene polyphenyl isocyanate), tetramethylxylene diisocyanate, toluene diisocyanate, any of which may be modified to include biuret, urethane, urea, carbamate, isocyanurate, or carbodiimide groups.
[0078] In a preferred embodiment, the aromatic polyisocyanate is a polymethylene polyphenyl isocyanate having an NCO content of 30.4% (according to DIN EN ISO 11 909).
[0079] Aromatic polyisocyanates are used at 0.2 to 2.0 wt% of the total weight of the adhesive composition, preferably 0.3 to 0.65 wt% of the total weight of the adhesive composition.
[0080] In a particularly preferred embodiment, the aromatic polyisocyanate is based on 0.3 to 0.65 wt% of a polymethylene polyphenyl isocyanate of the total weight of the adhesive composition, having an NCO content of 30.4% (according to DIN EN ISO 11909).
[0081] Isocyanate-functionalized silanes (E)
[0082] The adhesive composition of the present invention comprises at least one isocyanate-functionalized silane (E) in a total isocyanate-functionalized silane content of 0.2-3.0 wt% based on the total weight of the adhesive composition.
[0083] There are no particular limitations on isocyanate-functionalized silanes. Examples include those produced by reacting polyisocyanate compounds (such as toluene diisocyanate, methylene diphenyl diisocyanate) with a silane compound having the following formula:
[0084]
[0085] Where W is a group containing active hydrogen selected from the group consisting of hydroxyl, carboxyl, mercapto, primary amino, and secondary amino groups, X is a hydrolyzable alkoxy group, and R... 4 It is C1-C 20 Alkyl, C6-C 20 Aryl, C1-C 20 Aryl alkyl group, R is selected from C1-C 20 Hydrocarbon groups, especially propylene (-CH2-CH2-CH2-), and b is 0, 1, or 2.
[0086] More examples include:
[0087] • The reaction product of aminosilane and polyisocyanate;
[0088] • The reaction product of mercaptosilane and polyisocyanate;
[0089] • The reaction product of carboxylic acid ester-functionalized silanes and polyisocyanates;
[0090] • Isocyanate-functionalized silanes, such as (3-isocyanopropyl)trimethoxysilane.
[0091] The reaction products of aminosilanes and polyisocyanates are particularly preferred, especially secondary aminosilanes.
[0092] In a preferred embodiment, the isocyanate-functionalized silane is the reaction product of a secondary aminoalkoxysilane and a polyisocyanate, such as the reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret.
[0093] In a particularly preferred embodiment, the isocyanate-functionalized silane is the reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret, having an isocyanate content of 7%. The isocyanate-functionalized silane may contain additional inert additives, such as plasticizers.
[0094] Based on the total weight of the adhesive composition, the isocyanate-functionalized silane is present in 0.2-3 wt%, preferably 0.5 to 2.6 wt%, and more preferably 0.5-2.5 wt%.
[0095] In a particularly preferred embodiment, the isocyanate-functionalized silane is the reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret, having an isocyanate content of 7%, and is used at 0.8-1.0 wt%, preferably 0.5-2.5 wt%, based on the total weight of the adhesive composition.
[0096] Amine catalyst (F)
[0097] Based on the total weight of the adhesive composition, the adhesive composition of the present invention contains 0.1-0.6 wt% of (F) amine catalyst.
[0098] Amine catalysts are any amine catalysts capable of catalyzing the reaction of isocyanates with water. Preferred are tertiary amines, such as aliphatic cyclic and acyclic tertiary amines, including N,N-dimethylcyclohexaneamine, triethylenediamine, N,N,N,N-tetramethylalkylenediamine, N,N,N,N-pentamethyldiethylenetriamine, triethylamine, N,N-dimethylbenzylamine, N,N-dimethylhexadecylamine, N,N-dimethylbutylamine, and 2,2'-dimorpholinodiethyl ether.
[0099] 2,2'-dimorpholinodiethyl ether is particularly preferred.
[0100] The amine catalyst is used at 0.1-0.6 wt%, preferably 0.1 to 0.35 wt%, and more preferably 0.14 to 0.3 wt%, based on the total weight of the binder composition.
[0101] In a preferred embodiment, the amine catalyst is 0.14 to 0.3 wt% of 2,2'-dimorpholinodiethyl ether, based on the total weight of the binder composition.
[0102] Mercaptosilane (G)
[0103] Based on the total weight of the adhesive composition, the adhesive composition of the present invention comprises 0-1.5 wt% (G) of at least one mercaptosilane and / or 0-1.5 wt% (G') of at least one aminosilane, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0104] There are no particular limitations on the mercaptosilanes. Particularly preferred are mercaptosilanes having the following formula:
[0105]
[0106] Where R 1 R 2 and R 3 Independently selected from OCH3 and OC2H5;
[0107] And R 4 It is C nH 2n , where n is an integer from 1 to 12.
[0108] A particularly preferred option is a mercaptosilane, wherein R 1 R 2 and R 3 It is OCH3 and n is 1 to 6.
[0109] In a preferred embodiment, the mercaptosilane is γ-mercaptopropyltrimethoxysilane.
[0110] Based on the total weight of the adhesive composition, the at least one mercaptosilane is preferably present in a total mercaptosilane content of 0-1.5, more preferably 0.75 to 1.2 wt%, and particularly preferably 0.75 to 1.0 wt%.
[0111] In a particularly preferred embodiment, the at least one mercaptosilane is 0.75 to 1.0 wt% γ-mercaptopropyltrimethoxysilane, based on the total weight of the adhesive composition.
[0112] Aminosilane (G')
[0113] Based on the total weight of the adhesive composition, the adhesive composition of the present invention comprises 0-1.5 wt% (G) of at least one mercaptosilane and / or 0-1.5 wt% (G') of at least one aminosilane, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0114] There are no particular limitations on aminosilanes. Primary and secondary aminosilanes can be used. Secondary aminosilanes are particularly preferred, especially aminosilanes having the following formula:
[0115]
[0116] Where R 1 R 2 R 3 R 4 R 5 and R 6 Independently selected from OCH3 and OC2H5;
[0117] And R 7 and R 8 Selected independently from C n H 2n , where n is an integer from 1 to 6, preferably n is 3.
[0118] In a preferred embodiment, the at least one aminosilane is bis(γ-trimethoxysilylpropyl)amine.
[0119] Based on the total weight of the adhesive composition, the at least one aminosilane is preferably present in a total aminosilane content of 0-1.5 wt%, more preferably 0.01 to 0.5 wt%, more preferably 0.05 to 0.2 wt%, and more particularly preferably 0.1 to 0.15 wt%.
[0120] In a particularly preferred embodiment, the at least one aminosilane is 0.09 to 0.2 wt% bis(γ-trimethoxysilylpropyl)amine, based on the total weight of the adhesive composition.
[0121] Carbon black (H)
[0122] Based on the total weight of the adhesive composition, the adhesive composition of the present invention contains 10-35 wt% (H) carbon black.
[0123] There are no particular limitations on the carbon black used. Preferred carbon blacks exhibit a value of at least 80, preferably at least 90, and more preferably at least 95 cm⁻¹. 3 The oil absorption value of dibutyl phthalate / 100g carbon black, as measured according to ASTM D-2414-09. Additionally, the carbon black is expected to have an iodine value of at least 80, as determined by ASTM D1510-11.
[0124] Based on the total weight of the binder composition, carbon black is present in 10-35 wt%, preferably 17.6 to 25 wt%, and more preferably 20 to 23 wt%.
[0125] Calcium carbonate (I)
[0126] Based on the total weight of the adhesive composition, the adhesive composition of the present invention optionally contains 0-20 wt% (I) calcium carbonate. The calcium carbonate particles may be untreated or surface-modified by treatment with chemicals such as organic acids or esters of organic acids.
[0127] Preferably, calcium carbonate is present in 5 to 10 wt%, more preferably in 6 to 9 wt%, based on the total weight of the binder composition.
[0128] The total content of calcium carbonate plus fillers other than carbon black and calcium carbonate is 3-15 wt%, more preferably 5-12 wt%, based on the total weight of the composition.
[0129] Packing material (J)
[0130] Based on the total weight of the composition, the adhesive composition of the present invention optionally contains 0-15 wt% of additional fillers other than calcium carbonate and / or carbon black.
[0131] Examples of suitable fillers include fumed silica, clay, calcium oxide, organoclay, talc, frosted glass, ceramics such as boron nitride, metals, cross-linked organic polymers, and lignocellulose powder.
[0132] If fumed silica is used, the particles can be untreated or surface-modified by treatment with chemicals such as chlorosilanes, dichlorosilanes, alkyltrialkoxysilanes, or polydimethylsiloxanes.
[0133] The filler may be fumed silica and / or clay, which may be present in 0-20 wt%.
[0134] Based on the total weight of the composition, the total content of calcium carbonate plus filler (e.g., fumed silica and / or clay) is 0-20 wt%.
[0135] In a preferred embodiment, the adhesive composition of the present invention comprises 0.1-1 wt%, more preferably 0.2-0.75 wt%, and particularly preferably 0.3 to 0.6 wt% of filler, based on the total weight of the adhesive composition.
[0136] In a preferred embodiment, the filler is fumed silica, which is present at 0.1-1 wt%, more preferably 0.2-0.75 wt%, and particularly preferably 0.3 to 0.6 wt% based on the total weight of the binder composition.
[0137] Organometallic catalysts (K)
[0138] The binder contains at least one organometallic catalyst capable of catalyzing the reaction of isocyanates with functional groups having at least one active hydrogen atom and the condensation of silanes. Metal carboxylates include tin carboxylate and zinc carboxylate. Metal chain alkanoates include stannous octanoate, bismuth octanoate, or bismuth neodecanoate. Preferably, the at least one organometallic catalyst is an organotin catalyst. Examples include dibutyltin dilaurate, dimethyltin dinedecanoate, dimethyltin thiol, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin thiol, bis(2-ethylhexyl thioglycolate) dibutyltin, dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin thiol, dioctyltin dioctanoate, dioctyltin dinedecanoate, and dioctyltin dilaurate. In a particularly preferred embodiment, it is dimethyltin dinedecanoate.
[0139] Based on the total weight of the binder, the organometallic catalyst is preferably present in 0.001-2 wt%, more preferably 0.005-1 wt%, and particularly preferably 0.01 to 0.5 wt%.
[0140] In a particularly preferred embodiment, the organometallic catalyst is an organotin catalyst used at 0.01-0.5 wt% of the total weight of the binder, particularly those selected from those listed above.
[0141] In another preferred embodiment, the organometallic catalyst is dimethyltin neodecanoate used at 0.01-0.5 wt% of the total weight of the binder.
[0142] Other ingredients
[0143] The adhesive composition of the present invention may additionally contain other components, such as, for example, one or more plasticizers (such as diisononyl phthalate), one or more stabilizers, such as heat stabilizers, visible light stabilizers, and UV stabilizers.
[0144] Examples of heat stabilizers include alkyl-substituted phenols, phosphites, sebacic acid esters, and cinnamic acid esters. If present, preferred heat stabilizers are organophosphites, and more specifically, trinonylphenyl phosphite, as disclosed in U.S. Patent No. 6,512,033 (which is incorporated herein by reference). The heat stabilizer may comprise at least 0.01 or at least 0.3% by weight, up to a maximum of 5% by weight, up to a maximum of 2% by weight, or up to a maximum of 1.0% by weight, based on the total weight of the adhesive composition. The adhesive composition may be free of such heat stabilizers.
[0145] UV light stabilizers include benzophenone and benzotriazole. Specific UV light absorbers include those from BASF, such as TINUVIN. TM P, TINUVIN TM 326. TINUVIN TM 213, TINUVIN TM 327, TINUVIN TM 571, TINUVIN TM 328, and those from Cytec, such as CYASORB TM UV-9, CYASORB TM UV-24, CYASORB TM UV-1164, CYASORB TM UV-2337, CYASORB TM UV-2908, CYASORB TM UV-5337, CYASORB TM UV-531 and CYASORB TM UV-3638. Among these, TINUVIN TM571 is preferred. One or more UV light absorbers may constitute at least 0.1, at least 0.2, or at least 0.3 parts by weight of the adhesive composition, and may constitute up to 3, up to 2, or up to 1 part by weight.
[0146] The adhesive composition of the present invention may further comprise one or more visible light stabilizers. Preferred visible light stabilizers include hindered amine visible light stabilizers, such as TINUVIN, available from Cytec. TM 144. TINUVIN TM 622, TINUVIN TM 77. TINUVIN TM 123. TINUVINT M 765, CHIMASSORB TM 944; all purchased from Ciba-Geigy's CYASORB TM UV-500, CYASORB TM UV-3581, CYASORB TM UV-3346. Among these, TINUVIN TM 765 is a preferred choice. One or more visible light stabilizers may comprise at least 0.1, at least 0.2, or at least 0.3 parts by weight of the adhesive composition, and may comprise up to 3, up to 2, or up to 1.5 parts by weight.
[0147] In preferred embodiments, the stabilizer comprises trinonylphenyl phosphite, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol and mixtures thereof, with mixtures thereof being particularly preferred.
[0148] Viscosity
[0149] The viscosity of the adhesive composition is expressed as refractive viscosity, which is the amount of time (in seconds) it takes for 20g of the adhesive composition to pass through a 4.0mm orifice under a pressure of 552kPa at 23°C. The refractive viscosity can be, for example, at least 5 seconds, at least 10 seconds, at least 15 seconds, and can be, for example, up to 150 seconds, up to 120 seconds, up to 80 seconds, or up to 70 seconds.
[0150] Adhesive components
[0151] In one aspect, the present invention provides an adhesive assembly comprising:
[0152] Glass substrate;
[0153] Second substrate;
[0154] The adhesive composition of the present invention comprises a layer that is in adhesive contact with two substrates.
[0155] The second substrate is not particularly limited and can be, for example, glass, metal (especially metal with a primer), an electro-coated surface, a painted surface, wood, and cured polyurethane. In a preferred embodiment, the second substrate is selected from surfaces coated with automotive topcoat (metal coated with automotive topcoat), electro-coated surfaces, cured polyurethane, and cured silanized polyurethane.
[0156] In a particularly preferred embodiment, the components of the present invention include:
[0157] Glass substrate;
[0158] Substrate coated with automotive paint (such as silanized automotive paint);
[0159] The adhesive composition of the present invention comprises a layer that is in adhesive contact with two substrates.
[0160] Manufacturing method
[0161] The adhesive composition of the present invention is manufactured by mixing the components under inert and dry conditions and / or under vacuum until a homogeneous mixture is obtained.
[0162] In a preferred manufacturing method, a polyether prepolymer, an aminosilane (if used), an isocyanate silane, a diisononyl phthalate plasticizer (if used), an aliphatic isocyanate, an aromatic isocyanate, and a mercaptosilane (if used) are loaded into a mixer vessel (such as a Ross mixer) and heated to 60°C or about 60°C while being stirred under vacuum (e.g., for five minutes or about five minutes). An amine catalyst and an organometallic catalyst are added, and the mixture is stirred under vacuum (e.g., for five minutes or about five minutes). The vacuum is broken, and a filler (if used, such as fumed silica), carbon black, and calcium carbonate (if used) are added to the reactor under an inert atmosphere (e.g., N2 or Ar) and stirred (e.g., for 2-5 minutes). The filler (if used, such as fumed silica) may also be added to the mixer before the carbon and calcium carbonate. The mixture is placed under vacuum and stirred for a longer period of time (e.g., 15 minutes). Add the polyester prepolymer (preheated to 80°C or about 80°C) and stabilizer (if used) and re-establish the vacuum, then stir the mixture for another 5 minutes. The resulting adhesive composition can be packaged, for example, into airtight tubes, which are stored in nitrogen-filled, sealed aluminum bags.
[0163] use
[0164] The adhesive compositions of the present invention are particularly suitable for bonding glass to painted or coated substrates without the need for a primer.
[0165] In use, the adhesive is applied to a glass substrate and / or a second-coated substrate. If necessary, both substrates may be cleaned before applying the adhesive. The glass substrate and the second-coated substrate are then bonded together, with the adhesive of the present invention sandwiched between them.
[0166] Curing is affected by atmospheric humidity.
[0167] Particularly preferred embodiments
[0168] The following are particularly preferred embodiments of the adhesive composition of the present invention:
[0169] 1. A one-component polyurethane adhesive composition comprising:
[0170] (A) At least one polyether prepolymer with a total content of 30-75 wt% of polyether prepolymer;
[0171] (B) At least one polyester prepolymer with a total content of 0.5-2.0 wt% of polyester prepolymer;
[0172] (C) At least one aliphatic polyisocyanate with a total aliphatic polyisocyanate content of 0.5-3.0 wt%;
[0173] (D) At least one aromatic polyisocyanate with a total aromatic polyisocyanate content of 0.2-2.0 wt%;
[0174] (E) At least one isocyanate-functionalized silane with a total isocyanate-functionalized silane content of 0.2-3.0 wt%;
[0175] (F) 0.1-0.6 wt% amine catalyst;
[0176] (G) at least one mercaptosilane with a total mercaptosilane content of 0-1.5 wt% and / or at least one aminosilane with a total aminosilane content of 0-1.5 wt%, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0177] (H) 10-35wt% carbon black;
[0178] (I) Optional 0-20 wt% calcium carbonate;
[0179] (J)Optional 0-20 wt% of fillers other than carbon black and calcium carbonate;
[0180] (K) At least one organometallic catalyst, said catalyst being capable of catalyzing the reaction of isocyanates with functional groups having at least one active hydrogen and silane condensation;
[0181] The total polyisocyanate content is 1-5 wt%, the total amount of calcium carbonate and filler is 0-20 wt%, and the weight percentages are based on the total weight of the polyurethane adhesive.
[0182] 2. The adhesive composition according to Example 1, wherein the at least one polyether prepolymer (A) is manufactured by reacting one or more polyols in the presence of a polyisocyanate, preferably a diisocyanate, wherein the polyether polyol may be selected from polyether polyols, hydroxyl-containing polysulfides, polymeric polyols and mixtures thereof.
[0183] 3. The adhesive composition according to Example 1 or 2, wherein the at least one polyether prepolymer is manufactured by reacting a polyisocyanate with a polyether polyol.
[0184] 4. The adhesive composition according to Example 1, 2 or 3, wherein the polyether polyol is manufactured by reacting a polyisocyanate with a polyol selected from poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(butylene oxide) glycol and poly(tetrahydrofuran) glycol.
[0185] 5. The adhesive composition according to any of the foregoing embodiments, wherein the polyether prepolymer is manufactured by reacting a polyisocyanate selected from toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI) (hydrogenated MDI), isophorone diisocyanate (IPDI), and mixtures thereof with a difunctional polyether polyol selected from poly(epoxy)diols in which the alkylene derivatives are C2 to C4, a trifunctional polyol in which the alkylene derivatives are C2 to C4, and mixtures thereof, initiated by a trifunctional polyol.
[0186] 6. The adhesive composition according to any of the foregoing embodiments, wherein the polyether prepolymer comprises a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups (equivalent weight 1558) and a nominal difunctional poly(propylene oxide) having 56 hydroxyl groups (equivalent weight 1000) reacted with MDI.
[0187] 7. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyester prepolymer (B) is manufactured by reacting one or more linear copolyesters having primary hydroxyl functional groups with a polyisocyanate, preferably a diisocyanate.
[0188] 8. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyester prepolymer (B) is manufactured by reacting one or more linear copolyesters having primary hydroxyl functional groups with a polyisocyanate selected from: toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI) (hydrogenated MDI), isophorone diisocyanate (IPDI), and mixtures thereof.
[0189] 9. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyester prepolymer (B) is manufactured by reacting a copolyester with a molecular weight of 3,500 Da with MDI.
[0190] 10. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aliphatic polyisocyanate (C) is selected from isophorone diisocyanate, 1,6-hexamethylene diisocyanate, bis(4-isocyanocyclohexyl)methane and trimethylhexamethylene diisocyanate, any of which may be modified to include biuret, urethane, urea, carbamate, isocyanurate or carbodiimide groups.
[0191] 11. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aliphatic polyisocyanate (C) is based on an HDI trimer.
[0192] 12. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aromatic polyisocyanate (D) is selected from diphenylmethane diisocyanate (MDI), polymethylene polyphenyl isocyanate, polymeric MDI (PMDI, a mixture of diphenylmethane diisocyanate and polymethylene polyphenyl isocyanate), tetramethylxylene diisocyanate, toluene diisocyanate, any of which may be modified to include biuret, urethane, urea, carbamate, isocyanurate or carbodiimide groups.
[0193] 13. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aromatic polyisocyanate (D) is a polymethylene polyphenyl isocyanate.
[0194] 14. The adhesive composition according to any of the foregoing embodiments, wherein the at least one isocyanate-functionalized silane (E) is selected from silanes produced by reacting a polyisocyanate compound (such as toluene diisocyanate, methylene diphenyl diisocyanate) with an active hydrogen-containing group W of a silane compound having the following formula:
[0195]
[0196] Where W is a group containing active hydrogen selected from the group consisting of hydroxyl, carboxyl, mercapto, primary amino, and secondary amino groups, and X is a hydrolyzable alkoxy group. R 4 It is C1-C 20 Alkyl, C6-C 20 Aryl, C1-C 20 Aryl alkyl group, R is selected from C1-C 20 Hydrocarbon groups, especially propylene (-CH2CH2CH2-), and b is 0, 1, or 2.
[0197] 15. The adhesive composition according to any of the foregoing embodiments, wherein the at least one isocyanate-functionalized silane (E) is a reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret.
[0198] 16. The adhesive composition according to any of the foregoing embodiments, wherein the amine catalyst (F) is a tertiary amine catalyst.
[0199] 17. The adhesive composition according to any of the foregoing embodiments, wherein the amine catalyst (F) is selected from N,N-dimethylcyclohexane, triethylenediamine, N,N,N,N-tetramethylalkylenediamine, N,N,N,N-pentamethyldiethylenetriamine, triethylamine, N,N-dimethylbenzylamine, N,N-dimethylhexadecylamine, N,N-dimethylbutylamine, 2,2'-dimorpholinodiethyl ether, and mixtures thereof.
[0200] 18. The adhesive composition according to any of the foregoing embodiments, wherein the amine catalyst (F) is 2,2'-dimorpholinodiethyl ether.
[0201] 19. The adhesive composition according to any of the foregoing embodiments, wherein the at least one mercaptosilane (G) has the following formula:
[0202]
[0203] Where R 1 R 2 and R 3 Independently selected from OCH3 and OC2H5;
[0204] And R 4 It is -C n H 2n - where n is an integer from 1 to 12.
[0205] 20. The adhesive composition according to Example 19, wherein R 1 R 2 and R 3 It is OCH3 and n is 1 to 6.
[0206] 21. The adhesive composition according to any of the foregoing embodiments, wherein the at least one mercaptosilane (G) is γ-mercaptopropyltrimethoxysilane.
[0207] 22. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aminosilane (G') has the following formula:
[0208]
[0209] Where R 1 R 2 R 3 R 4 R 5 and R 6 Independently selected from OCH3 and OC2H5;
[0210] And R 7 and R 8 Independently selected from -C n H 2n - where n is an integer from 1 to 6.
[0211] 23. The adhesive composition according to Example 22, wherein n is 3.
[0212] 24. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyether prepolymer is present at 45-65 wt% based on the total weight of the adhesive composition.
[0213] 25. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyether prepolymer is present at 58-64 wt% based on the total weight of the adhesive composition.
[0214] 26. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyester prepolymer is present at 0.9-1.5 wt% based on the total weight of the adhesive composition.
[0215] 27. The adhesive composition according to any of the foregoing embodiments, wherein the at least one polyester prepolymer is present at 1 to 1.3 wt% based on the total weight of the adhesive composition.
[0216] 28. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aliphatic polyisocyanate is present at 0.5-3.0 wt% based on the total weight of the adhesive composition.
[0217] 29. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aliphatic polyisocyanate is present at 0.8-2.5 wt% based on the total weight of the adhesive composition.
[0218] 30. The adhesive composition according to any of the foregoing embodiments, wherein the at least one aromatic polyisocyanate is present in 0.3 to 0.65 wt% based on the total weight of the adhesive composition.
[0219] 31. The adhesive composition according to any of the foregoing embodiments, wherein the at least one isocyanate-functionalized silane is present at 0.5-2.8 wt% based on the total weight of the adhesive composition.
[0220] 32. The adhesive composition according to any of the foregoing embodiments, wherein the at least one isocyanate-functionalized silane is present at 0.5-2.5 wt% based on the total weight of the adhesive composition.
[0221] 33. The adhesive composition according to any of the foregoing embodiments, wherein the amine catalyst is present in 0.1-0.6 wt% based on the total weight of the adhesive composition.
[0222] 34. The adhesive composition according to any of the foregoing embodiments, wherein the amine catalyst is present in 0.14 to 0.3 wt% based on the total weight of the adhesive composition.
[0223] 35. The adhesive composition according to any of the foregoing embodiments, wherein the mercaptosilane is present in 0.75 to 1.2 wt% based on the total weight of the adhesive composition.
[0224] 36. The adhesive composition according to any of the foregoing embodiments, wherein the mercaptosilane is present at 0.75 to 1.0 wt% based on the total weight of the adhesive composition.
[0225] 37. The adhesive composition according to any of the foregoing embodiments, wherein the aminosilane is present in 0.05 to 0.5 wt% based on the total weight of the adhesive composition.
[0226] 38. The adhesive composition according to any of the foregoing embodiments, wherein the aminosilane is present in 0.09 to 0.2 wt% based on the total weight of the adhesive composition.
[0227] 39. The adhesive composition according to any of the foregoing embodiments, wherein the aminosilane is present in 0.1 to 0.15 wt% based on the total weight of the adhesive composition.
[0228] 40. The adhesive composition according to any of the foregoing embodiments, wherein carbon black is present in 17.6 to 25 wt% based on the total weight of the adhesive composition.
[0229] 41. The adhesive composition according to any of the foregoing embodiments, wherein carbon black is present in 20 to 23 wt% based on the total weight of the adhesive composition.
[0230] 42. The adhesive composition according to any of the foregoing embodiments, wherein calcium carbonate is present in 6 to 9 wt% based on the total weight of the adhesive composition.
[0231] 43. The adhesive composition according to any of the foregoing embodiments, wherein the at least one organometallic catalyst is an organotin catalyst.
[0232] 44. The adhesive composition according to any of the foregoing embodiments, wherein the at least one organometallic catalyst is selected from dibutyltin dilaurate, dimethyltin dineodecanate, dimethyltin thiol, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin thiol, dibutyltin bis(2-ethylhexyl thioglycolate) dibutyltin, dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin thiol, dioctyltin dioctanoate, dioctyltin dineodecanate, dioctyltin dilaurate, and mixtures thereof.
[0233] 45. The adhesive composition according to any of the foregoing embodiments, wherein the at least one organometallic catalyst is dimethyltin dinedecanoate.
[0234] 46. The adhesive composition according to any of the foregoing embodiments, wherein the at least one organometallic catalyst is used at 0.01 to 0.05 wt% based on the total weight of the adhesive composition.
[0235] 47. The adhesive composition according to any of the foregoing embodiments further comprises a heat stabilizer, a visible light stabilizer, and a UV light stabilizer.
[0236] 48. The adhesive composition according to any of the foregoing embodiments further comprises a stabilizer selected from: trinonylphenyl phosphite, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol and mixtures thereof.
[0237] 49. The adhesive composition according to any of the foregoing embodiments, further comprising at least one plasticizer.
[0238] 50. The adhesive composition according to any of the foregoing embodiments further comprises at least one plasticizer, said plasticizer being diisononyl phthalate.
[0239] 51. An adhesive composition comprising:
[0240] (A) At least one polyether prepolymer comprising a total content of 45-65 wt% of a polyether prepolymer, said polyether prepolymer comprising a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups (equivalent weight 1558) and a nominal difunctional poly(propylene oxide) having 56 hydroxyl groups (equivalent weight 1000) reacting with MDI.
[0241] (B) At least one polyester prepolymer with a total content of 0.5-2.0 wt%, said polyester prepolymer being produced by reacting a copolyester with a molecular weight of 3,500 Da with MDI.
[0242] (C) At least one aliphatic polyisocyanate based on HDI trimer, with a total aliphatic polyisocyanate content of 0.75-2.5 wt%;
[0243] (D) At least one aromatic polyisocyanate with a total aromatic polyisocyanate content of 0.2-2.0 wt%, wherein the aromatic polyisocyanate is a polymethylene polyphenyl isocyanate;
[0244] (E) At least one isocyanate-functionalized silane with a total isocyanate-functionalized silane content of 0.5 to 2.6 wt%, said silane being a reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret;
[0245] (F) 0.1 to 0.35 wt% of an amine catalyst, wherein the amine catalyst is 2,2'-dimorpholinodiethyl ether;
[0246] (G) At least one mercaptosilane with a total mercaptosilane content of 0-1.5 wt%, said mercaptosilane being γ-mercaptopropyltrimethoxysilane, and / or at least one aminosilane with a total aminosilane content of 0-1.5 wt%, said aminosilane being bis(γ-trimethoxysilylpropyl)amine, wherein the combination of amino and / or mercaptosilane is at least 0.5 wt%.
[0247] (H) 10-35wt% carbon black;
[0248] (I) Optional 0-20 wt% calcium carbonate;
[0249] (J)Optional 0-20 wt% of fillers other than carbon black and calcium carbonate;
[0250] (K) at least one organometallic catalyst, wherein the organometallic catalyst is dimethyltin dinedecanoate;
[0251] The total polyisocyanate content is 1-5 wt%, the total amount of calcium carbonate and filler is 0-20 wt%, and the weight percentages are based on the total weight of the polyurethane adhesive.
[0252] 52. An adhesive composition comprising:
[0253] (A) At least one polyether prepolymer comprising a total content of 58-64 wt% of a polyether prepolymer, said polyether prepolymer comprising a nominal trifunctional poly(propylene oxide) (equivalent to 1558 wt%) having 36 hydroxyl groups reacting with MDI and a nominal difunctional poly(propylene oxide) (equivalent to 1000 wt%) having 56 hydroxyl groups.
[0254] (B) At least one polyester prepolymer having a total content of 1 to 1.3 wt% of polyester prepolymer, said polyester prepolymer being produced by reacting a copolyester with a molecular weight of 3,500 Da with MDI.
[0255] (C) At least one aliphatic polyisocyanate based on HDI trimer, with a total aliphatic polyisocyanate content of 0.8-2.5 wt%;
[0256] (D) At least one aromatic polyisocyanate with a total aromatic polyisocyanate content of 0.3 to 0.65 wt%, wherein the aromatic polyisocyanate is a polymethylene polyphenyl isocyanate;
[0257] (E) At least one isocyanate-functionalized silane with a total isocyanate-functionalized silane content of 0.5-2.5 wt%, said silane being a reaction product of N,N-bis[(3-trimethoxysilyl)-propyl]amine reacted with HDI-biuret;
[0258] (F) 0.14 to 0.3 wt% of an amine catalyst, wherein the amine catalyst is 2,2'-dimorpholinodiethyl ether;
[0259] (G) At least one mercaptosilane with a total mercaptosilane content of 0.75 to 1.0 wt%, said mercaptosilane being γ-mercaptopropyltrimethoxysilane, and / or at least one aminosilane with a total aminosilane content of 0.1 to 0.15 wt%, said aminosilane being bis(γ-trimethoxysilylpropyl)amine, wherein the combination of amino and / or mercaptosilane is at least 0.7 wt%;
[0260] (H) 20 to 23 wt% carbon black;
[0261] (I) 6 to 12 wt% calcium carbonate;
[0262] (J) 0.3 to 0.6 wt% fumed silica;
[0263] (K) 0.01 to 0.05 wt% of at least one organometallic catalyst, wherein the organometallic catalyst is dimethyltin dinedecanoate;
[0264] The total polyisocyanate content is 1.0-4.0 wt%, the total amount of calcium carbonate and filler is 3-15 wt%, and the weight percentages are based on the total weight of the polyurethane adhesive.
[0265] 53. An adhesive assembly comprising:
[0266] Glass substrate;
[0267] Second substrate;
[0268] A layer of the adhesive composition described in any of the foregoing embodiments, the layer being in adhesive contact with two substrates.
[0269] 54. A method for bonding a glass substrate to a second-coated substrate, the method comprising the steps of:
[0270] (1) Provide a glass substrate and a second coated substrate;
[0271] (2) Apply the adhesive composition of any one of Examples 1 to 52 to the glass substrate, the second coated substrate, or both;
[0272] (3) Assemble the glass substrate and the second coated substrate such that the adhesive is bonded to both substrates.
[0273] Example
[0274]
[0275] Polyether prepolymer (A): Under nitrogen atmosphere, 363.68 g of Voranol 220-056 polyol, 527.04 g of Voranol 232-036 polyol, and 32 g of diisononyl phthalate were charged into a 4-liter reactor, mixed, and heated to 54°C. All subsequent steps were carried out under nitrogen atmosphere. 160.64 g of molten MDI was added and mixed. 0.08 g of stannous octoate catalyst was added dropwise. The temperature in the reactor increased due to the exothermic reaction; the reaction mixture was maintained between 80°C and 90°C for 30 minutes. The reaction mixture was then cooled to 60°C, and 501.20 g of diisononyl phthalate and 15.36 g of diethyl malonate were added and mixed for 30 minutes, followed by cooling to room temperature. The resulting polyether-based polyurethane prepolymer has an isocyanate content of 1.25% by weight and a viscosity of 16,000 cps at 23°C, as measured by the procedure disclosed in column 12, lines 38 to 49 of U.S. Patent No. 5,922,809.
[0276] Polyester prepolymer (B): Under nitrogen atmosphere, 280 g of diisononyl phthalate was placed in a container and heated to 50°C. 172.80 g of MDI was added, followed by the slow addition of molten Dynacoll 7381. The mixture was stirred and allowed to react between 80°C and 90°C for 40 minutes. The resulting prepolymer was cooled and stored under an inert atmosphere. Based on the total weight of the prepolymer, the polyester prepolymer has an NCO content of 2 wt%.
[0277] Isocyanate-functionalized silane (E): The reaction product of a secondary aminoalkoxysilane and a polyisocyanate was prepared by charging 333.3 g of diisononyl phthalate into a reactor under nitrogen atmosphere. 729.75 g of Desmodur N-100 (a solvent-free aliphatic polyisocyanate resin based on hexamethylene diisocyanate-biuret) was added, and the mixture was thoroughly mixed and purged under a nitrogen cover. 436.95 g of N,N-bis[(3-trimethoxysilyl)propyl]amine was slowly added to the mixture, and the mixture was reacted under nitrogen atmosphere for 30 minutes. Based on the total weight of the adduct, the adduct had an isocyanate content of 7.1 wt%.
[0278] stabilizer mixture
[0279] 140g of Tinuvin 765, 140g of Tinuvin 571, and 120g of Doverphos 4 were loaded into a reactor and mixed under nitrogen. The mixture was stirred under nitrogen for 60 minutes and then stored under an inert atmosphere.
[0280] Preparation of adhesive compositions
[0281] Using the proportions listed in Table 2, calcium carbonate, silica, and carbon black were mixed and dried at 204°C for approximately 20 hours, and then cooled in a sealed container to form a filler mixture. The polyether prepolymer, aminosilane, isocyanate-functionalized silane, diisononyl phthalate, aliphatic polyisocyanate, aromatic polyisocyanate, and mercaptosilane were loaded into a 2-gallon mixer preheated to approximately 60°C. The mixture was degassed and mixed under vacuum for 5 minutes. The vacuum was broken with nitrogen, and then DMDEE and the tin catalyst, along with any stabilizers, were added, followed by further degassed and mixing under vacuum for 10 minutes. The vacuum was broken again with nitrogen, and then the filler mixture, including silica (if used), was added to the mixer. Mixing was initiated to wet the filler for 2 minutes. Vacuum was applied and mixing continued for 15 minutes. After breaking the vacuum with nitrogen, the mixture was scraped off, and the polyester prepolymer, along with any stabilizers, was added. Mixing under vacuum continued for 10 minutes. The resulting adhesive composition was packaged into airtight tubes, which were then stored in nitrogen-filled, sealed aluminum bags.
[0282] Quick-dry adhesive
[0283] The tests were conducted on the following samples:
[0284] 1-inch x 6-inch or 1-inch x 4-inch glass, with one side covered with ceramic frit 2L-5350, a bismuth-based bending frit purchased from Johnson Matthey Inc.;
[0285] 1-inch x 4-inch metal coated with Axalta RK8032 2k polyurethane varnish;
[0286] 1-inch x 4-inch metal coated with BASF 2K4 2k polyurethane varnish;
[0287] 1-inch x 4-inch metal coated with Axalta GenIV silanized varnish;
[0288] Windshield with a bent enamel frit;
[0289] The rapid knife adhesion test is performed by distributing beads measuring 6mm (width) × 6mm (height) × 100mm (length) onto a test substrate. The rapid knife test is run after the beads have initially cured at 23°C and 50% RH (relative humidity) for a specific period and after any further environmental exposure. During the test, a slit (20-40mm) is cut between the adhesive end and the substrate. The cured bead is then cut into the test substrate at a 60-degree angle with a razor blade while simultaneously pulling back the end of the bead at a >90-degree angle. Notches are cut into the substrate approximately every 3-5mm. Adhesion is evaluated as adhesive failure (AF), film failure (TF), and / or cohesive failure (CF). In the case of AF, the cured bead can be separated from the surface of the test substrate, while in CF, separation occurs within the sealant adhesive due to cutting and pulling, and TF is a special case of CF in which a film of cured adhesive remains on the substrate after cutting and testing.
[0290] Unless otherwise specified, the pressure viscosity on the adhesive sample is measured by determining the amount of time (in seconds) it takes for 20 g of the adhesive composition to pass through a 4.0 mm orifice under a pressure of 552 kPa at 23°C.
[0291] The lap shear test was performed according to the SAE J1529 test procedure described below. Triangular beads of adhesive composition, approximately 10 mm in base and 10 mm in height, were applied along a 25 mm × 100 mm width of a specified specimen (such as a bismuth-based bent glass frit specimen) and approximately 6 mm from the end of the specimen. A second substrate, which may be a painted metal specimen, was immediately pressed onto the adhesive beads to obtain a final height of 6 mm of the composition in the middle. Unless otherwise specified, the specimen was cured for 7 days at 23°C and 50% relative humidity (RH). The specimen was then pulled at a rate of 50 mm / min using an Instron tester immediately or after further environmental exposure. The load (lbs) at specimen breakage was divided by the specimen area (in mm). 2 The lap shear bond strength (psi) is obtained. Adhesion is evaluated as adhesive failure (AF), film failure (TF), and / or cohesive failure (CF). In the case of AF, the cured beads can be separated from the surface of the substrate being tested, while in CF, separation occurs within the sealant adhesive, and TF is a special case of CF in which a film of cured adhesive is left on the substrate after the test.
[0292] Circular cakes of adhesive samples were cured for 7 days at 23°C and 50% relative humidity (RH). Test specimens were cut from these cured sample cakes, and tensile strength, elongation, and Young's modulus (from 1% to 10% strain) were tested using an Inström tester, all according to ASTM D412 (die C).
[0293] Sagging performance was evaluated using the following method. A metal panel, 10 cm high and 30 cm long, was placed vertically along its length. The adhesive composition, before or after heat aging conditions, was distributed as right-angled triangular beads along the top edge of the panel at a height of 1.8 cm and a base of 0.6 cm. After 30 minutes, the amount of dripping or sagging from the tip of the adhesive beads was measured in millimeters. If no sagging occurred from the bead tip, the sagging test result was zero millimeters.
[0294]
[0295]
[0296] The results showed that even after 14 days of humidity treatment and 10 days of heat aging at 90°C, the adhesive of the present invention exhibited 100% cohesive failure with all substrates.
[0297] Table 4 shows the initial viscosity, heat-aged viscosity, heat-aged sagging, tensile strength, elongation, and Young's modulus of Examples 1 to 4.
[0298]
[0299] All samples from Examples 1 to 4 show zero sag, tensile strength greater than 900 psi, elongation greater than 300%, and Young's modulus greater than 3 MPa after 3 days of heat aging at 54°C.
[0300] Table 5 shows the overlap shear bonding data for Examples 2 and 3.
[0301]
[0302] It has an overlap shear strength greater than 400 psi and exhibits 100% cohesive failure.
Claims
1. A one-component polyurethane adhesive composition comprising: (A) At least one polyether prepolymer with a total content of 30-75 wt%; (B) At least one polyester prepolymer with a total content of 0.5-2.0 wt%; (C) At least one aliphatic polyisocyanate in a total content of 0.5-3.0 wt%; (D) At least one aromatic polyisocyanate in a total content of 0.2-2.0 wt%; (E) At least one isocyanate-functionalized silane in a total content of 0.2-3.0 wt%; wherein the isocyanate-functionalized silane is a reaction product of N,N-bis[(3-trimethoxysilyl)propyl]amine and HDI-biuret; (F) Amine catalyst with a content of 0.1-0.6 wt%; (G) at least one mercaptosilane in a total content of 0-1.5 wt%, and (G') at least one aminosilane in a total content of 0-1.5 wt%, wherein the combination of aminosilane and mercaptosilane comprises at least 0.5 wt%; (H) Carbon black with a content of 10-35 wt%; (I) Calcium carbonate, which may be present in a concentration of 0-20 wt%; (J) Fillers other than carbon black and calcium carbonate, which may be present in an optional amount of 0-20 wt%; (K) At least one organometallic catalyst, said catalyst being capable of catalyzing the reaction of isocyanates with functional groups having at least one active hydrogen and silane condensation; The total content of polyisocyanates is 1-5 wt%, and the total content of calcium carbonate and fillers is 0-20 wt%. All weight percentages mentioned above are based on the total weight of the polyurethane adhesive.
2. The adhesive composition according to claim 1, wherein, The at least one polyether prepolymer (A) is manufactured by polymerizing one or more polyols in the presence of a polyisocyanate, wherein the one or more polyols are optionally selected from polyether polyols, hydroxyl-containing polysulfides, polymeric polyols, and mixtures thereof.
3. The adhesive composition according to claim 2, wherein, The polyisocyanate is a diisocyanate.
4. The adhesive composition according to claim 1, wherein, The at least one polyether prepolymer is manufactured by reacting a polyisocyanate with a polyether polyol.
5. The adhesive composition according to claim 1, wherein, The polyether prepolymer is manufactured by reacting a polyisocyanate with a polyol selected from the following: poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(butane oxide) glycol, poly(tetrahydrofuran) glycol, poly(ethylene oxide) triol, poly(propylene oxide) triol, poly(butane oxide) triol, poly(tetrahydrofuran) triol, and mixtures thereof.
6. The adhesive composition according to claim 1, wherein, The polyether prepolymer is produced by reacting a polyisocyanate selected from toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI), isophorone diisocyanate (IPDI), and mixtures thereof with a difunctional polyether polyol selected from poly(epoxide)diols in which the alkylene derivatives are C2 to C4, a trifunctional polyol in which the alkylene derivatives are C2 to C4, and mixtures thereof, initiated by a trifunctional polyol.
7. The adhesive composition according to claim 1, wherein, The polyether prepolymer comprises a nominal trifunctional poly(propylene oxide) having 36 hydroxyl groups and a nominal difunctional poly(propylene oxide) having 56 hydroxyl groups, having reacted with MDI, wherein the nominal trifunctional poly(propylene oxide) has an equivalent weight of 1558 and the nominal difunctional poly(propylene oxide) has an equivalent weight of 1000.
8. The adhesive composition according to claim 1, wherein, The at least one polyester prepolymer (B) is manufactured by reacting one or more linear copolyesters having primary hydroxyl functional groups with a polyisocyanate.
9. The adhesive composition of claim 8, wherein the polyisocyanate is a diisocyanate.
10. The adhesive composition according to claim 1, wherein, The at least one polyester prepolymer (B) is manufactured by reacting one or more linear copolyesters having primary hydroxyl functional groups with a polyisocyanate selected from: toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene dicyclohexyl isocyanate (HMDI), isophorone diisocyanate (IPDI), and mixtures thereof.
11. The adhesive composition according to claim 1, wherein, The at least one polyester prepolymer (B) is produced by reacting a copolyester with a molecular weight of 3,500 Da with MDI.
12. The adhesive composition according to claim 1, wherein, The at least one aliphatic polyisocyanate (C) is selected from isophorone diisocyanate, 1,6-hexamethylene diisocyanate, bis(4-isocyanocyclohexyl)methane and trimethylhexamethylene diisocyanate, any of which may be modified to include biuret, urethane, urea, carbamate, isocyanurate or carbodiimide groups.
Citation Information
Patent Citations
One-part moisture curable polyurethane adhesive
US5922809A
Polyurethane sealant compositions
US6512033B1
Isocyanate functional adhesive wihich bonds primerless to silanated acrylic polyol based coating
CN111344326A
Polyurethane adhesive compositions
WO2019156737A1